Alterations in Kainate Receptor and TRPM1 Localization in Bipolar Cells after Retinal Photoreceptor Degeneration - Gayet-Primo, Jacqueline; Puthussery, Theresa (Frontiers in Cellular Neuroscience, 2015)
Photoreceptor degeneration differentially impacts glutamatergic signaling in downstream On and Off bipolar cells. In rodent models, photoreceptor degeneration leads to loss of glutamatergic signaling in On bipolar cells, whereas Off bipolar cells appear to retain glutamate sensitivity, even after extensive photoreceptor loss. The localization and identity of the receptors that mediate these residual glutamate responses in Off bipolar cells have not been determined. Recent studies show that macaque and mouse Off bipolar cells receive glutamatergic input primarily through kainate-type glutamate receptors. Here, we studied the impact of photoreceptor degeneration on glutamate receptor associated proteins in Off and On bipolar cells. We show that the kainate receptor subunit, GluK1, persists in remodeled Off bipolar cell dendrites of the rd10 mouse retina. However, the pattern of expression is altered and the intensity of staining is reduced compared to wild-type retina. The kainate receptor auxiliary subunit, Neto1, also remains in Off bipolar cell dendrites after complete photoreceptor degeneration. Similar preservation of kainate receptor subunits was evident in human retina in which photoreceptors had degenerated due to serous retinal detachment. In contrast, photoreceptor degeneration leads to loss of synaptic expression of TRPM1 in mouse and human On bipolar cells, but strong somatic expression remains. These findings demonstrate that Off bipolar cells retain dendritic glutamate receptors during retinal degeneration and could thus serve as a conduit for signal transmission from transplanted or optogenetically-restored photoreceptors.